Bone marrow adipocytes – Good, bad, or just different?. Issue 4 (July 2021) - Nandy, Ananya; Rendina-Ruedy, Elizabeth
Abstract : Skeletal remodeling is essential for proper maintenance of adult bone mass, and due to its heavy energetic demands this process is closely tied to whole body metabolic. Thus, bone formation by the osteoblast, bone resorption by the osteoclast, and mechano-sensing by the osteocyte, are highly coupled processes that are essential for bone turnover. When one experiences a disruption in these processes, over time increased skeletal fragility and fracture can result. In addition to these primary cells, secondary cells within the skeletal niche are suspected to directly coordinate bone health as well. The bone marrow compartment provides a unique microenvironment in which communication occurs between white blood cells, red blood cells, platelets, and immune cells, in addition to classic bone cells (osteoblasts, osteoclasts, and osteocytes) that can both directly and indirectly impact skeletal homeostasis. One such cell population that has attracted much attention and scientific inquiry in the past decade are bone marrow adipocytes (BMAdipo) which can be found interspersed throughout the marrow compartment, and collectively are often referred to as bone marrow adipose tissue (BMAT). Although our understanding of BMAT has advanced significantly in the past decade, many questions remain relative to their lineage and function. The current collection presents recent studies and the up-to-date understanding of bone marrow adipocytes, along with future clinical perspectives related to this unique depot.